Simulation Based Study of Oxygen Plasma Induced Defects on Zigzag Graphene Nanoribbons. (25th October 2017) - Chen, Po-An; Lee, Jia-Wei; Chiang, Meng-Hsueh; Hsu, Wei-Chou
Abstract : As the 2D materials are being developed for the era of the internet of things, a complete solution of integrated circuits including electronics devices and interconnects is needed. This work investigates the design issues and insights of the graphene interconnects with the defects stemming from oxygen plasma etching. The density functional theory and non-equilibrium Green's function are used for simulations to investigate how the carrier transport mechanism is affected by the defects, including edge-roughness, oxygen-on-edge, and sp 3 -type cases. Design techniques to relieve the impact of defects are also provided.